2019
DOI: 10.1371/journal.pone.0219483
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase 4 mediates TGF-β1/Smad signaling pathway induced acute kidney injury in hypoxia

Abstract: Hypoxia is an important cause of acute kidney injury (AKI) in various conditions because kidneys are one of the most susceptible organs to hypoxia. In this study, we investigated whether nicotinamide adenine dinucleotide 3-phosphate (NADPH) oxidase 4 (Nox4) plays a role in hypoxia induced AKI in a cellular and animal model. Expression of Nox4 in cultured human renal proximal tubular epithelial cells (HK-2) was significantly increased by hypoxic stimulation. TGF-β1 was endogenously secreted by hypoxic HK-2 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 36 publications
0
29
1
Order By: Relevance
“…Myocardial fibrogenesis is induced by TGF-b1 (13,15,(24)(25)(26). To test whether TGF-b1 is increased in deceased COVID-19 patients, we measured TGF-b1 mRNA levels by quantitative RT-PCR in left ventricular tissue taken from patients with COVID-19.…”
Section: Fibrotic Markers Are Increased In Deceased Covid-19 Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial fibrogenesis is induced by TGF-b1 (13,15,(24)(25)(26). To test whether TGF-b1 is increased in deceased COVID-19 patients, we measured TGF-b1 mRNA levels by quantitative RT-PCR in left ventricular tissue taken from patients with COVID-19.…”
Section: Fibrotic Markers Are Increased In Deceased Covid-19 Patientsmentioning
confidence: 99%
“…TGF-b1 binding to its receptor leads to phosphorylation of intracellular SMAD3, which upregulates profibrotic genes (15,24,25), resulting in increased expression of collagens or fibronectin. Although altered levels of SMAD3 RNA would not necessarily equate to altered SMAD3 activity, it has been shown in a variety of tissues that TGF-b1-induced upregulation of SMAD3 can be an important inducer of reactive oxygen species (ROS) via upregulation of NADPH oxidases II and IV (NOX2/NOX4) (25)(26)(27)(28)(29). We therefore measured SMAD3 in left ventricular tissue from deceased COVID-19 patients and found the mRNA levels to be significantly increased (Figure 1E).…”
Section: Fibrotic Markers Are Increased In Deceased Covid-19 Patientsmentioning
confidence: 99%
“…NOX4 expression in proximal tubular cells increased after exposure to high glucose, and NOX4 inhibition with GKT136901 decreased albuminuria in diabetic mice [ 28 , 29 ]. NOX4 deficiency was associated with the increased tubular injury after IRI [ 30 ], and hypoxia to kidney tubule cell upregulated NOX4 expression via a TGF-β1/Smad signaling pathway [ 31 ]. NOX2 also plays a role especially in the development of diabetic nephropathy, and its expression was upregulated in the kidneys of diabetic mice [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NOX is composed of a membrane subunit (NOX1-5) and catalytic subunits of p47phox, p22phox, p67phox. Growing studies con rmed that NOX4 is widely expressed in renal tubular epithelial cells, and abnormal expression of NOX4 is closely related to renal tubular damages [43,44]. It has been reported that glycosylated albumin can induce the up-regulation of NOX4 expression, leading to brosis and apoptosis in NRK-52E cells, and promoting the development of DN [45].…”
Section: Discussionmentioning
confidence: 99%